2009
DOI: 10.1152/ajpregu.90925.2008
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin increases brain and muscle mitochondrial biogenesis and exercise tolerance

Abstract: Davis JM, Murphy EA, Carmichael MD, Davis B. Quercetin increases brain and muscle mitochondrial biogenesis and exercise tolerance. Am J Physiol Regul Integr Comp Physiol 296: R1071-R1077, 2009. First published February 11, 2009 doi:10.1152/ajpregu.90925.2008.-Quercetin is one of a broad group of natural polyphenolic flavonoid substances that are being investigated for their widespread health benefits. These benefits have generally been ascribed to its combination of antioxidant and anti-inflammatory activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
336
5
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(361 citation statements)
references
References 33 publications
16
336
5
4
Order By: Relevance
“…Specifically, betaine has been linked to improving muscular endurance, strength, and power (31,55) and can be found in beetroot. Likewise, the polyphenols, quercetin and resveratrol, which are found in beetroot have, in some instances, been reported to increase aerobic capacity and stimulate mitochondrial biogenesis (20,44). Although we do not rule out the potential for NO 3 Ϫ to operate synergistically with these compounds, the unchanged plasma [NO 2 Ϫ ], diastolic BP, MAP, and V O 2 response following PL supplementation suggests that NO 3 Ϫ is the key "bioactive" compound in BR.…”
Section: Experimental Considerationsmentioning
confidence: 77%
“…Specifically, betaine has been linked to improving muscular endurance, strength, and power (31,55) and can be found in beetroot. Likewise, the polyphenols, quercetin and resveratrol, which are found in beetroot have, in some instances, been reported to increase aerobic capacity and stimulate mitochondrial biogenesis (20,44). Although we do not rule out the potential for NO 3 Ϫ to operate synergistically with these compounds, the unchanged plasma [NO 2 Ϫ ], diastolic BP, MAP, and V O 2 response following PL supplementation suggests that NO 3 Ϫ is the key "bioactive" compound in BR.…”
Section: Experimental Considerationsmentioning
confidence: 77%
“…In mammals, flavonoids exert various biological and pharmacological effects [10]. Several studies have indicated that quercetin may have anti-inflammatory and antioxidant properties [8] due to its free radical scavenging and metal chelating activities [23]. In addition, this compound exerts a potent antioxidant effect.…”
Section: Introductionmentioning
confidence: 99%
“…The quercetin in this investigation was combined with vitamin C and niacin to improve quercetin bioavailability, as explained in the Methods. The quercetin dose is based on animal studies showing increased mitochondrial biogenesis beginning at 12.5 mg quercetin·(kg body mass) -1 (Davis et al 2009). …”
Section: Introductionmentioning
confidence: 99%